Prognostic Value of Adrenomedullin and Natriuretic Peptides in Uroseptic Patients Induced by Ureteroscopy - Wei Hu; Pang-hu Zhou; Wei Wang; Lijun Zhang; Xiao-bin Zhang (Mediators of Inflammation)
The aim of this paper is to investigate whether urosepsis is related to irrigation pressure of ureteroscopy (URS) and evaluate the prognostic value of adrenomedullin (ADM) and atrial and brain natriuretic peptides (ANP and BNP) in URS-induced uroseptic patients. From July 2008 to October 2013, we enrolled 332 patients with untreated unilateral ureteral obstruction (UUO). The UUO group included three subgroups of, respectively, 118, 132, and 82 patients who underwent URS under intermittent stable irrigation pressure of, respectively, 80, 120, and 160 mmHg. The plasma concentrations of ADM, ANP, and BNP were measured in all subjects. URS was performed for all UUO patients; the values of the three peptides were measured again after URS. Irrigation pressure and stone size were independent risk factors of urosepsis. After URS, the plasma concentrations of ADM, ANP, and BNP were significantly higher in uroseptic patients. Moreover, the concentrations were significantly higher depending on the disease severity. Plasma concentrations of the three peptides were correlated with plasma ET concentration in the uroseptic patients. The areas under receiver operating characteristic (ROC) curve of ADM, ANP, and BNP for predicting urosepsis were 0.811, 0.728, and 0.764, respectively. In conclusion, ADM, along with ANP and BNP, is valuable for prognosis in urosepsis secondary to URS which is associated with irrigation pressure.